Telomerases : chemistry, biology and clinical applications - Lue, Neal F., 1962-; Autexier, Chantal, 1963- (Hoboken : John Wiley & Sons, 2012)
"This book is a comprehensive and up-to-date review and evaluation of the contemporary status of telomerase research. Chapters in this volume cover the basic structure, mechanisms, and diversity of the essential and regulatory subunits of telomerase. Other topics include telomerase biogenesis, transcriptional and post-translational regulation, off-telomere functions of telomerase and the role of telomerase in cellular senescence, aging and cancer. Its relationship to retrotransposons, a class of mobile genetic elements that shares similarities with telomerase and serves as telomeres in selected organisms, are also reviewed"--Provided by publisher.
The telomerase complex : an overview / Johanna Mancini and Chantal Autexier -- Telomerase RNA : structure, function, and molecular mechanisms / Yehudi Tzfati and Julian J.-L. Chen -- TERT structure, function, and molecular mechanisms / Emmanuel Skordalakes and Neal F. Lue -- Telomerase biogenesis : RNA Processing, trafficking and protein Interactions / Tara Beattie and Pascal Chartrand -- Transcriptional regulation of human telomerase / Antonella Farsetti and Yu-Sheng Cong -- Telomerase regulation and telomere length homeostasis / Joachim Lingner and David Shore -- Telomere structure in telomerase regulation / Momchil D. Vodenicharov and Raymund J. Wellinger -- Off-telomere functions of telomerase / Kenkichi Masutomi and William C. Hahn -- Murine Models of Dysfunctional Telomeres and Telomerase / Yie Liu and Lea Harrington -- Cellular senescence, telomerase, and cancer in human cells / Phillip G. Smiraldo [and others] -- Telomerase, retrotransposons, and evolution / Irina R. Arkhipova.
Includes bibliographical references and index.
Print version record.
Keywords: Telomerase -- Physiology; Telomerase -- Metabolism; Telomerase -- Genetics; Geriatrics; Natural history; Science; SCIENCE -- Life Sciences -- Molecular Biology; SCIENCE -- Life Sciences -- Genetics & Genomics; Science; Telomerase; Electronic books; Electronic books